A Study on Whether Assistive Devices Are Needed for Dementia Elderly in Dementia Day Care Centre - Safawi, Nur Balqis Ahmad; Rahim, Asiah Abdul; Zen, Ismawi (International Journal of Natural Sciences Research, 2015)
The aim of this paper is to seek whether there is a current or future need for the devices to be used in dementia day care centre based on the Malaysian context. This is due to the community has not yet familiarize with such devices for cognitive use as there is limitation in terms of reaching the product itself in the local market. Moreover, there are few research studies linking the needs of dementia, people and their acknowledgement of utilizing the gadgets. Dementia is a mental illness that demonstrates a decrease in cognitive capacity and memory, which generally affects the seniors. Studies show that the number of elderly affected with dementia keep rising and this phenomenon has grabbed a lot of people’s attention. Due to this matter, there are a lot of experimental and exploration researches being conducted that are correlated with assistive devices for this cohort. For this research, observations, checklist and interview session were used as instruments for data collection. Two of the dementia day care centers were selected as the case studies. Assistive device is a tool designed to facilitate and enhance human capabilities for everyday use basis. Its existence is proven to bring tremendous help for people with disability to help them to be independent and carry on with their daily routine, analyze the collected data of the study regarding whether there are needs for the devices to be included in the dementia day care center program. Suggestions and recommendations for future research were given in the end based on the conclusions achieved.